Enhancement of photocatalytic degradation of organic dyes using ZnO decorated on reduced graphene oxide (rGO) - Pang, Yean Ling; Tee, Su Fang; Lim, Steven; Abdullah, Ahmad Zuhairi; Ong, Hwai Chyuan; Wu, Chien Hou; Chong, Woon Chan; Mohammadu, Abdul Wahab; Mahmoudi, Ebrahim (Desalination Publications, 2018)
Reduced graphene oxide (rGO) with excellent electron capturing ability could be coupled with semiconductor photocatalyst to prevent the recombination problem of photogenerated hole–electron pairs encountered by pure zinc oxide (ZnO) while simultaneously promote the photocatalytic activity. In this study, rGO decorated with ZnO (ZnO/rGO) photocatalyst was synthesized for the photocatalytic degradation of rhodamine B, congo red and methyl orange in water. The ZnO and ZnO/rGO photocatalysts were characterized by using field emission scanning microscopy-energy dispersive X-ray analysis and X-ray powder diffraction, and Fourier transformed infrared spectroscopic analyses. The morphology and elemental results showed that both catalysts were in spherical shape and free from impurities. It was found that the average particle size of ZnO/rGO was smaller than that of pure ZnO which indicated that ZnO decorated on graphene sheet would decrease the particle size. Congo red showed the highest degradation efficiency and it was attributed to the rapid break down of its azo bond (–N=N–) and aromatic rings by hydroxyl radicals. It was found that 97.96% degradation could be achieved in 1 h under optimum conditions which were at 10 mg/L of initial congo red concentration, 2 g/L of ZnO/rGO catalyst dosage and a solution pH of 7. The spent ZnO/rGO exhibited high catalytic activity of 96.67% at optimum conditions indicating its high stability to act as a photocatalyst. The photocatalytic degradation of congo red satisfactorily fitted a pseudo-first-order reaction kinetic. Besides, the removal of chemical oxygen demand for congo red after 1 h of photocatalytic degradation was nearly 100%.